Impact of psychosocial profile on alopecia areata in pediatric patients: A case control study from a tertiary care hospital in Eastern Uttar Pradesh - Neerja Saraswat; Pooja Shankar; Ajay Chopra; Sushil Kumar; Debdeep Mitra; Reetu Agarwal (Indian Journal of Dermatology, 2020)
Background: Alopecia areata (AA) is a common form of nonscarring alopecia characterized by patchy loss of hair from the scalp and body. It is a complex outcome of factors such as autoimmunity, genetic factors, infectious diseases, as well as psychological factors, such as stress, personality type, familial conditions. Around 20% of patients are in the pediatric age group, and 60% of the patients develop AA before the age of 20 years. Aim: The present study looked into the impact of psychosocial factors in AA. Materials and Methods: This was a case-control study conducted over a period of 1 year. One hundred and two patients and age and gender-matched control group between the ages of 2 and 14 years were included. A questionnaire was administered to identify the stress arising due to personal or familial conditions, school-related issues, psychotrauma or illness, and accidents prior to developing AA. Age and gender-matched patients with other dermatoses with low psychosomatic component to it and unlikely to be influenced by stress were selected as control. Result: Fifty-three patients (52 %) were male and 49 were female (48 %). Fifty-five (53.9%) patients were in the age group of 10 to 14 years. Forty (39.2%) children had multiple patches. Onset was <5 months in 30 patients (29.4%). Forty-nine (48%) children reported stress due to school-related issues compared to 13 (12.7%) in the control group. Eighteen (17.6%) children had familial issues compared to 6 (0.05%) in the control group. Nineteen children (18.6%) had multiple stressors. Sixty-nine (67.6%) patients related their disease to a stress component compared to 33 (32.3%) who could not relate to any stress. A significant association was noted between examination pressure and academic performance with onset of AA compared to control (P < 0.05%), which was stronger among female compared to male. Conclusion: The psychological profile and comorbidities have a significant impact on the onset or recidivism of AA. Impact of a stressful personal or family life, parental pressure to perform better in school, and psychological vulnerability can significantly contribute to the onset or exacerbation of AA.